AB0980 Long term tolerability and effectiveness of a single injection of 6ml hylan G-F 20 in 451 patients with knee osteoarthritis pain. (23rd January 2014) - Wagner, J.-P.; Bonacker, G.; Wolf, H.; Frömel, M.; Leonhardt, K.; Schulz, A.
Abstract : Objectives: To determine the tolerability and effectiveness of a single injection of 6 ml hylan G-F 20 treatment in patients with symptomatic Osteoarthritis (OA) in standard clinical practice over a period of 1 year. Methods: 91 orthopaedic and trauma surgeons in Germany recorded tolerability and short term effectiveness in knee OA patients receiving a single intra-articular injection of 6 ml hylan G-F 20 one week after treatment. Then, patients were followed up by standardized telephone interview through an independent observer. Tolerability, knee OA pain (reported on a 5-Point Likert-Scale), patients' global assessment and quality of life (SF12) were obtained after 3, 6, 9 and 12 months. Results: 451 patients [Age: 61, 98 years (mean); BMI: 27, 82 (mean); Female: 50, 4%; Knee OA Grade III: 51, 9%; Grade II: 38, 8%; Grade I: 9, 3%] met the inclusion/exclusion criteria out of 571 patients which have been enrolled. Tolerability was assessed on all 571 patients and treatment-related adverse events (AEs) were observed in 1, 93% of patients. None of these AEs was serious. Telephone follow-up was possible in 243, 237, 199 and 148 patients after 3, 6, 9 and 12 months. Knee OA pain significantly decreased already one week after the injection and showed a significant improvement over 12 months (p≤0, 001 at each timepoint). Also patients' global assessment at all timepoints and assessment of physical composites score of the SF 12 at 3, 6, 9 and 12 months showed significant improvement (p≤0, 001). Mental composite score of the SF 12 showed significant improvement after 9 and 12 month (p≤0, 05). Physicians assessed the results of a single injection of 6 ml hylan G-F 20 as "very well" and "well" in 79, 1% of the treated patients. High baseline pain value was identified as a potential predictor of hylan G-F 20 effectiveness by logistic regression. Only 20 patients (8.5%) were re-treated with hylan G-F 20 at month 9 or 12. Conclusions: A single injection of 6 ml hylan G-F 20 is a well-tolerated treatment option in patients with symptomatic knee osteoarthritis with a low incidence of local, treatment-related AEs. A significant reduction of knee OA pain was observed as early as one week after the injection and was durable for the whole follow up period of 12 months. The single injection of 6 ml hylan G-F 20 allows a reduced risk of injection-associated joint infections, and its fast onset of lasting pain relief provides an important therapeutical benefit in daily practice. Disclosure of Interest: J.-P. Wagner Grant/Research support from: Genzyme, G. Bonacker Grant/Research support from: Genzyme, H. Wolf Grant/Research support from: Genzyme, M. Frömel Grant/Research support from: Genzyme, K. Leonhardt Grant/Research support from: Genzyme, A. Schulz Employee of: Genzyme